Text-fig. 3. a–e: Berberis auriolensis sp. nov. a: Oriolo MSF 644, Holotype. b: Oriolo MSF 794, asterisks indicate position of teeth. c: Oriolo MSF 784. d: Oriolo MSF 789. e: Oriolo MSF 790. f–h: Modern leaves of Berberis. f: Berberis amurensis var. japonica modern leaf (NMNS Cleared Leaf Database specimen T 0454). g: Berberis koreana modern leaf (NMNS Cleared Leaf Database specimen T 1646). h: Berberis canadensis modern leaf (NMNS Cleared Leaf Database specimen T 1670). i: Epimedium cf. praeaspera Oriolo MSF 778, asterisk indicates position of tooth. j: Clematis aff. vitalba Oriolo MSF 630. Scale bars 10 mm (a–j). in The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome - Denk, Thomas; Sami, Marco; Teodoridis, Vasilis; Martinetto, Edoardo (Zenodo, 2022)
Text-fig. 3. a–e: Berberis auriolensis sp. nov. a: Oriolo MSF 644, Holotype. b: Oriolo MSF 794, asterisks indicate position of teeth. c: Oriolo MSF 784. d: Oriolo MSF 789. e: Oriolo MSF 790. f–h: Modern leaves of Berberis. f: Berberis amurensis var. japonica modern leaf (NMNS Cleared Leaf Database specimen T 0454). g: Berberis koreana modern leaf (NMNS Cleared Leaf Database specimen T 1646). h: Berberis canadensis modern leaf (NMNS Cleared Leaf Database specimen T 1670). i: Epimedium cf. praeaspera Oriolo MSF 778, asterisk indicates position of tooth. j: Clematis aff. vitalba Oriolo MSF 630. Scale bars 10 mm (a–j). Published as part of Denk, Thomas, Sami, Marco, Teodoridis, Vasilis & Martinetto, Edoardo, 2022, The Late Early Pleistocene Flora Of Oriolo, Faenza (Italy): Assembly Of The Modern Forest Biome, pp. 217-262 in Fossil Imprint 78 (1) on page 224, DOI:10.37520/fi.2022.009, http://zenodo.org/record/7167867